2020
DOI: 10.1139/cjb-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ABA and NaCl on physiological responses in selected bryophyte species

Abstract: The effects of NaCl and ABA on selected bryophyte species were studied. Two phylogenetically unrelated halophyte mosses, namely, Entosthodon hungaricus and Hennediella heimii, in addition of one model non-halophyte moss, Physcomitrella patens, were selected to compare the variability in certain biochemical and physiological parameters under salt-stress alone and salt-stress upon ABA pretreatment. The results showed different patterns of ABA effects in all three studied species, as well as no common response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
3
8
0
Order By: Relevance
“…Previous reports also demonstrated that ABA essentially triggered the antioxidant enzyme activities in angiosperms wheat and maize in response to drought stress (Wei et al, 2015;Yao et al, 2019). A lower level of ABA contributed to the activation of enzymatic antioxidant system in liverwort M. polymorpha, moss P. patens, A. undulatum, Entosthodon hungaricus and Hennediella heimii (Vujicic et al, 2017;Ćosić et al, 2020b). The ABAmediated enhancement of antioxidant enzyme activities was also reported in aquatic seaweed (Guajardo, Correa & Contreras-Porcia, 2016), indicating that the mechanisms was initiated earlier than the terrestrial plant.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports also demonstrated that ABA essentially triggered the antioxidant enzyme activities in angiosperms wheat and maize in response to drought stress (Wei et al, 2015;Yao et al, 2019). A lower level of ABA contributed to the activation of enzymatic antioxidant system in liverwort M. polymorpha, moss P. patens, A. undulatum, Entosthodon hungaricus and Hennediella heimii (Vujicic et al, 2017;Ćosić et al, 2020b). The ABAmediated enhancement of antioxidant enzyme activities was also reported in aquatic seaweed (Guajardo, Correa & Contreras-Porcia, 2016), indicating that the mechanisms was initiated earlier than the terrestrial plant.…”
Section: Discussionmentioning
confidence: 91%
“…Even though it is not clear when the ABA signaling transduction pathway emerged, the number of core components as well as distinct specialized functions have increased to adapt to the terrestrial habitat during land plant evolution (Furst-Jansen et al, 2020;Komatsu et al, 2020). ABA, a key mediator of the abiotic stress response, is responsible for regulating biochemical, metabolic and physiological mechanisms in response to environmental cues, including salt stress ( Cosi c et al, 2020). Despite the multigenic nature of salinity tolerance, we report here that the miR1047-based feedback control of the PpDCL1a transcript is one of the key components of salt stress adaptation in P. patens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports also demonstrated that ABA essentially triggered the antioxidant enzyme activities in angiosperms wheat and maize in response to drought stress ( Wei et al, 2015 ; Yao et al, 2019 ). A lower level of ABA contributed to the activation of enzymatic antioxidant system in liverwort M. polymorpha and mosses P. patens, A. undulatum, Entosthodon hungaricus , and Hennediella heimii ( Vujicic et al, 2017 ; Ćosić et al, 2020b ). The ABA-mediated enhancement of antioxidant enzyme activities was also reported in aquatic seaweed ( Guajardo, Correa & Contreras-Porcia, 2016 ), indicating that the mechanisms was initiated earlier than the terrestrial plant.…”
Section: Discussionmentioning
confidence: 99%